2023
DOI: 10.2147/rmhp.s400385
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Outpatient Payment Reforms on Volume and Expenditures in Public Hospitals: Evidence from a Quasi-Experimental Analysis in Zhejiang, China

Abstract: Purpose China developed an innovative episode-based payment scheme for outpatient care, namely “Ambulatory Patient Groups (APGs) + capitation” payment, to constrain inflation in outpatient expenditures. This study aimed to assess the effects of this payment method on volume and expenditures in Chinese public hospitals. Methods A quasi-experimental study was conducted with 7 municipal and 12 county hospitals from Jinhua as the intervention group and 15 municipal and 24 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…A DID analysis of medical expenses revealed that the ‘other expenses’ for planned cesarean sections in the treatment group decreased significantly compared to the control group. Consequently, our findings closely align with those of Zhang Tao [ 27 ], suggesting that the implementation of the SDP can play a significant role in controlling the proportion of consumable costs.…”
Section: Discussionsupporting
confidence: 88%
“…A DID analysis of medical expenses revealed that the ‘other expenses’ for planned cesarean sections in the treatment group decreased significantly compared to the control group. Consequently, our findings closely align with those of Zhang Tao [ 27 ], suggesting that the implementation of the SDP can play a significant role in controlling the proportion of consumable costs.…”
Section: Discussionsupporting
confidence: 88%
“…Post the DRG-PPS, the bundled payment method may further incentivize medical service providers to curtail costs to enhance revenue. 19 Table 2 delineated the estimated impact of reform on healthcare costs. Column (1) showed a discernible effect of the reform in reducing healthcare costs.…”
Section: Resultsmentioning
confidence: 99%
“…Post the DRG-PPS, the bundled payment method may further incentivize medical service providers to curtail costs to enhance revenue. 19 2)-( 5), DRG payments lead to a 13% reduction in drug costs and a 12.5% reduction in material costs.…”
Section: Healthcare Costsmentioning
confidence: 99%